Recent Temporal Dynamics in Economics: Empirical Analyses of Annual Publications in Economic Fields - Lutz Bornmann; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2024)
Differences in annual publication counts may reflect the dynamic of scientific progress. Declining annual numbers of publications may be interpreted as missing progress in field-specific knowledge. In this paper, we present empirical results on dynamics of progress in economic fields (defined by JEL codes) based on a methodological approach introduced by Bornmann and Haunschild (2022). We focused on publications that have been published between 2012 and 2021 and identified those fields in economics with the highest dynamics (largest rates of change in paper counts). We found that the field with the largest paper output across the years is 'Economic Development'. The results reveal that the field-specific rates of changes are mostly similar. However, the two fields 'Production and Organizations' and 'Health' show point estimators which are clearly higher than the estimators for the other fields. We investigated the publications in 'Production and Organizations' and 'Health' in more detail.
Keywords: A10; A12; A14; 330; scientometrics; bibliometrics; dynamics of research fields; economics; JEL code